Too much medicine in older people? Deprescribing through shared decision making. (3rd June 2016) - Jansen, Jesse; Naganathan, Vasi; Carter, Stacy M; McLachlan, Andrew J; Nickel, Brooke; Irwig, Les; Bonner, Carissa; Doust, Jenny; Colvin, Jim; Heaney, Aine; Turner, Robin; McCaffery, Kirsten
Abstract : Jansen and colleagues explore the role of shared decision making in tackling inappropriate polypharmacy in older adults